Physics on the rotating Earth - Saleh, Najm Abdola (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: In this thesis we study physics on the rotating Earth by studying the moving coordinate systems and rotating coordinate systems. First, we illustrate briefly some kind of translations like Galilean transformation which consists of two inertial frames, one of them moving with respect the other stationary We show how to transform between the two reference frames. Then we give the Lorentz transformations in which time is no more absolute when the speed approaches to the speed of light. We review Abelian and Non-Abelian groups. But then we will focus on the Newton’s equations of motion on the Earth and we will explain in details the derivation of these equations. We derive both the Coriolis and centrifugal forces. Later on we explain some applications about rotating Earth. The most important example is a projectile motion. We illustrate by derivation how it is the best way to show the reason of the deflections of missiles in long range distances. Another famous example is the Foucault pendulum, which is an important example to prove that the Earth is rotating about its axis. And finally, we give some applications to show the effect of Coriolis and centrifugal forces in our daily life. Keywords: Coriolis and Centrifugal Force, Foucault Pendulum. …………………………………………………………………………………………………………………………………………………………………………………………………………ÖZ: Hareketli ve dönen koordinat sistemlerinin dünya üzerindeki fiziğe etkileri incelenmiştir.Önce birbirine göre hareketli Galile koordinat sistemleri göz önüne alınmıştır.İki koordinat sistemi arasındaki dönüşüm verilmiştir.Işık hızına yakın durumlarda, ki zamanın mutlak özelliği geçersiz olur Lorentz dönüşümleri ele alınmıştır. Abel/ Abel olmayan gruplar gözden geçirilmiştir.Dönen dünya üzerindeki Newton hareket denklemleri ile Coriolis ve merkezkaç kuvetler türetilmiştir. Fırlatılmış cisimlerde dönmenin etkileri incelenmiştir. Uzun menzilli roket hareketindeki sapmalar iyi bir örnek olarak ele alınmıştır .Foucauft sarkacı dünyanin dönme etkisine başka bir önemli örnek teşkil etmekte olup dünyanın dönüşünü de kanıtlamaktadır.Coriolis ve merkezkaç kuvetlerinin günlük hayatımızdaki örnekleri irdelenmiştir. Anahtar Kelimeler: Coriolis ve Merkezkaç Kuvetleri, Foucault Sarkacı.
Master of Science in Physics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2013. Supervisor: Prof. Dr. Mustafa Halilsoy.
Keywords: Physics; Coriolis and Centrifugal Force, Foucault Pendulum